Effect of detoxification methods on ABE production from corn stover hydrolysate by Clostridium acetobutylicum CICC 8016. (18th February 2020) - Wang, Fengqin; Dong, Yuheng; Cheng, Xiang; Xie, Hui; Song, Andong; Zhang, Zhanying
Abstract: In this study, effects of different single biomass derived inhibitors on acetone–butanol–ethanol (ABE) production by Clostridium acetobutylicum CICC 8016 were first investigated. The results showed that formic acid, coumaric acid, and furfural at 0.5 g/L (sodium formate equivalent) inhibited ABE production. Furthermore, corn stover hydrolysate media were prepared following dilute acid pretreatment, enzymatic hydrolysis, and detoxification with different methods. Among overliming, steam stripping, acetone–ethyl ether extraction, and ion exchange with five anion resins, adsorption with resin D301 showed the highest efficiency for inhibitor removal (99–100% of phenolics and 87–99% of sugar degradation products). Without detoxification, ABE production was lower than 1.0 g/L from 28.1 g/L sugars whereas ABE production with medium detoxified by D301 resin achieved higher ABE concentrations and yields than control with synthetic medium. Correlation analysis further revealed that formic acid, coumaric acid, and total phenolics were the major compounds inhibiting ABE production. The results also showed that the single detoxification method was sufficient to detoxify the hydrolysate for ABE production at the pretreatment conditions used in this study. Abstract : Formic acid, coumaric acid and total phenolics were the major compounds inhibiting ABE production from corn stover hydrolysate and resin D301 showed the highest efficiency for inhibitor removal and ABE production.